Implementasi Program Literasi Digital bagi Siswa SMA dan SMK di Kabupaten Gorontalo Utara - Edson Yahuda Putra; Reynoldus Sahulata; Budi Harwanto; Rolly Junius Lontaan; Heris Hantu; George Morris William Tangka (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of information and communication technology requires students to have adequate digital literacy skills. However, preliminary observations in North Gorontalo Regency revealed that the use of digital technology by high school and vocational school students was not accompanied by a good understanding of digital ethics, personal data security, hoaxes, and digital footprints. The objective of this community service program is to improve students' digital literacy so they can use technology wisely, critically, ethically, and responsibly. The implementation method employed an educative and participative approach through direct socialization equipped with pre-test and post-test. The activity was conducted on 16–18 December 2025 at three partner schools, namely SMA Negeri 10 Gorontalo Utara, SMA Negeri 4 Gorontalo Utara, and SMK Negeri 3 Gorontalo Utara, with a total of 120 valid respondents. The evaluation results showed an increase in the average score from 2.53 (pre-test) to 4.45 (post-test), or an increase of 1.92 points (75.7%), with 86.7% of participants showing improvement and no participants experiencing a decline. The activity has proven effective in improving students' digital literacy and strengthening cooperation between universities and partner schools.